Partially orthogonal resonators for magnetic resonance imaging - Chacón-Caldera, Jorge; Malzacher, Matthias; Schad, Lothar R. (Scientific reports, 2017)
Resonators for signal reception in magnetic resonance are traditionally planar to restrict coil material and avoid coil losses. Here, we present a novel concept to model resonators partially in a plane with maximum sensitivity to the magnetic resonance signal and partially in an orthogonal plane with reduced signal sensitivity.